Neuroprotective Natural Molecules, From Food to Brain - González-Fuentes, Joaquin; Selva, Jorge; Moya, Carmen; Castro-Vázquez, Lucia; Lozano, Maria V.; Marcos, Pilar; Plaza-Oliver, Maria; Rodríguez-Robledo, Virginia; Santander-Ortega, Manuel J.; Villaseca-González, Noemi; Arroyo-Jimenez, Maria M. (Frontiers in Neuroscience, 2018)
The prevalence of neurodegenerative disorders is increasing; however, an effective neuroprotective treatment is still remaining. Nutrition plays an important role in neuroprotection as recently shown by epidemiological and biochemical studies which identified food components as promising therapeutic agents. Neuroprotection includes mechanisms such as activation of specific receptors, changes in enzymatic neuronal activity, and synthesis and secretion of different bioactive molecules. All these mechanisms are focused on preventing neuronal damage and alleviating the consequences of massive cell loss. Some neuropathological disorders selectively affect to particular neuronal populations, thus is important to know their neurochemical and anatomical properties in order to design effective therapies. Although the design of such treatments would be specific to neuronal groups sensible to damage, the effect would have an impact in the whole nervous system. The difficult overcoming of the blood brain barrier has hampered the development of efficient therapies for prevention or protection. This structure is a physical, enzymatic and efflux barrier that efficiently protects the brain from exogenous molecules. Therefore, the development of new strategies, like nanocarriers, that help to promote the access of neuroprotective molecules to the brain, is needed for providing more effective therapies for the disorders of the central nervous system (CNS). In order both to trace the success of these nanoplatforms on the release of the bioactive cargo in the CNS and determinate the concentration at trace levels of targets biomolecules by analytical chemistry and concretely separation instrumental techniques, constitute an essential tool. Currently, these techniques are used for the determination and identification of natural neuroprotective molecules in complex matrixes at different concentration levels. Separation techniques such as chromatography and capillary electrophoresis, using optical and/or mass spectrometry detectors, provide multiples combinations for the quantitative and qualitative analysis at basal levels or higher concentrations of bioactive analytes in biological samples. The development of food neuroprotective molecules as brain therapeutic agents is a complex task that requires the intimate collaboration and engagement of different disciplines. This work reviews the new advances achieved in the area towards a better understanding of the current state of the art and highlights promising approaches for brain neuroprotection.